Kinematic analysis in team-handball jump throw - Wagner, H.; Buchecker, M.; Müller, E. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purposes of our study were to determine the proximal-to-distal sequence of the linear joint and angular velocities and to measure the influence of maximal angular velocities and performance level to ball release speed of the jump throw, which is the most applied throwing technique in team-handball (Wagner et al., 2008).